2017
DOI: 10.3906/sag-1602-136
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the serum, liver, and renal cortical lipids and electrolytesin rabbits with cisplatin-induced nephrotoxicity

Abstract: Background/aim: Cisplatin is an anticancer drug that can induce nephrotoxicity. Its toxicity is associated with dyslipidemia and disturbed electrolyte balance. In the present study we investigated the changes in serum lipid profile and electrolyte levels and their contents in kidney and liver tissues of rabbits treated with cisplatin.Materials and methods: Twenty-eight adult male New Zealand White rabbits were used in the experiment. Animals of groups C, P1, and P2 were injected with saline, cisplatin (4.0 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Consistent with our study, Abdel-Gayoum et al (2017) concluded that cisplatin injection increases cholesterol, triglycerides (TG), and low-density lipoprotein (LDL). On the other hand, it was observed that the amount of high-density lipoprotein (HDL) in rabbits receiving Cisplatin decreased (32). Cameron et al (2020) also reported that cisplatin chemotherapy increases cholesterol, LDL, and TG in men with testicular cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, Abdel-Gayoum et al (2017) concluded that cisplatin injection increases cholesterol, triglycerides (TG), and low-density lipoprotein (LDL). On the other hand, it was observed that the amount of high-density lipoprotein (HDL) in rabbits receiving Cisplatin decreased (32). Cameron et al (2020) also reported that cisplatin chemotherapy increases cholesterol, LDL, and TG in men with testicular cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…LDL plays a key role in transporting cholesterol from the liver to peripheral cells, according to previous research ( Eckardstein, 2020 ). Moreover, several studies have demonstrated an inverse relationship between the concentration of CHOL ( Abdel-Gayoum and Ahmida, 2017 ) and LDL ( Ogunmoyole et al, 2019 ) in the liver and their corresponding levels in serum. Thus, our results suggest that CHOL accumulation and storage in the liver may be impaired in rats with hemizygous BDNF deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The renal tubules regulate the serum levels of electrolytes by reabsorbing them. In an experimental study on CIS nephrotoxicity, renal losses were believed to be the cause of hypomagnesemia, hypocalcemia, and hypokalemia [28]. Goren et al noted that electrolyte imbalances may be influenced by the cumulative dose of CIS [29].…”
Section: Discussionmentioning
confidence: 99%